WHEN TERRITORY DETERMINES CARE: THE UNEQUAL DISTRIBUTION OF HEALTH PROFESSIONALS AND ITS DIRECT IMPACTS ON LIFE AND DEATH IN REMOTE REGIONS - da Costa, João Carlos Tavares; Mendes, Everaldo dos Santos; Lourenço, Nelzo Moda Neto (Seven Editora, 2026)
This study analyzes how excessive exposure to crime-related news in the media impacts the social perception of criminal severity and modulates institutionalized penal responses. The exploratory bibliographic research examines specialized literature addressing the relationships between media, the social construction of criminal reality, and penal responses. The findings reveal that the trivialization of crime by the media operates through mechanisms of narrative selectivity, sensationalism, and the simplification of structural complexities, which reshape public perceptions of crime. The study identifies a central paradox: trivialization simultaneously trivializes and radicalizes perceptions of crime, generating desensitization that coexists with intensified demands for harsher penal responses. The analysis demonstrates that trivialization does not remain confined to the symbolic domain but penetrates penal institutions, compromising fundamental guarantees of impartiality. The implications for the legitimacy of democratic penal systems are profound, suggesting the need to base decisions on penal severity on rational analyses of effectiveness, rather than on reactions to media pressures that distort criminal realities.